Flexible Interconnection Device Planning of Low-Voltage Distribution Station Areas Based on Improved Supply Capability Indicators - ZHANG Rui, LIU Hengchao, ZHANG Guoju, GE Xuefeng, YU Miao (Dianli jianshe, 2025)
[Objective] To realize the reasonable planning of low-voltage flexible interconnection devices，effectively solve the problem of load imbalance in distribution station areas，and improve the supply capability of distribution networks，a supply capability assessment method considering the load distribution characteristics of distribution networks is proposed. Furthermore，a flexible interconnection device planning model for low-voltage distribution station areas that comprehensively considers the power-supply capability，construction efficiency，and economy of distribution networks is proposed. [Methods] First，a model of the distribution network supply capability with load growth is established，and an evaluation index for the efficiency of distribution network supply capability improvement is derived. Next，a flexible interconnection device planning framework considering the improvement of supply capability，economy，and load transfer constraints under distribution network reconfiguration is established and solved based on the non-dominated sorting genetic algorithms-II. [Results] The results of the case study of the IEEE 14 bus system with contact switches show that the planning model based on the proposed indicators can effectively improve the supply capability of the distribution network under actual load distribution. [Conclusions] Compared with traditional power-supply capacity indicators，the indicators proposed in this study can effectively reflect the objective law of actual load distribution and growth in the station areas. The planning method based on the proposed indicators can significantly improve the power-supply capacity of the distribution network. The proposed indicators show that the access of flexible interconnection devices in low-voltage station areas can gradually eliminate the bottlenecks of power supply caused by the imbalance of the load ratio in station areas and realize the efficient use of distribution network resources.